Assets returns volatility and investment horizon: the french case - Frédérique Bec; Christian Gollier (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper explores French assets returns predictability within a VAR setup. Using quarterly data from 1970Q4 to 2006Q4, it turns out that bonds, equities and bills returns are actually predictable. This feature implies that the investment horizon does indeed matter in the asset allocation. The VAR parameters estimates are then used to compute real returns conditional volatility across investment horizons. The results reveal the same kind of horizon effect as the one found in recent empirical studies using quarterly U.S. data. More specifically, the excess annualized standard deviation of French stocks returns with respect to bills and bonds returns decreases as the investment horizon grows. They suggest that long-horizon investors overstate the share of bonds in their portfolio choice when neglecting the horizon effect on risk of asset returns predictability.
Keywords: G11; 330; asset return predictability; investment horizon; vector autoregression; Kapitalertrag; Prognose; Institutioneller Anleger; Portfolio-Management; VAR-Modell; Schätzung; Frankreich